2019
DOI: 10.1111/ijau.12158
|View full text |Cite
|
Sign up to set email alerts
|

Loan loss provisions in large publicly quoted European banks and auditor independence

Abstract: The European Commission, citing deficiencies in the financial statements of banks during the financial crisis, has questioned the independence of the auditors of European banks at the onset of the crisis. We test for evidence of impaired auditor independence by examining if the economic bond between auditors and clients is associated with the audit quality of banks, controlling for the strength of banking regulation of the country in which a bank operates. We find no evidence of income‐increasing loan loss pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The increased uncertainty leads to more dispersed data that is fed into the ECL-models. Research has shown that there is no connection between the provision for credit losses and auditor-client economic bond (Kanagaretnam et al 2010;Campa and Donnelly 2019). It is expected that the auditor will place more emphasis on the provision for credit losses due to the increased uncertainty and will share an independent view on the models and assumptions that are used by the banks.…”
Section: Quantitative Analysis On Expected Credit Lossesmentioning
confidence: 99%
“…The increased uncertainty leads to more dispersed data that is fed into the ECL-models. Research has shown that there is no connection between the provision for credit losses and auditor-client economic bond (Kanagaretnam et al 2010;Campa and Donnelly 2019). It is expected that the auditor will place more emphasis on the provision for credit losses due to the increased uncertainty and will share an independent view on the models and assumptions that are used by the banks.…”
Section: Quantitative Analysis On Expected Credit Lossesmentioning
confidence: 99%
“…Strong banks governance is paramount for the whole financial system (Jizi & Nehme, 2018). In addition, the audit of banks is more complex than the one in other industries due to the complexity of their operations (Campa & Donnelly, 2019). Thus, audit committees play an important role in overseeing the financial reporting process and the auditing process.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we control for the magnitude of the discretionary loan loss provision ( DLLP ), a proxy of banks' financial reporting quality (Campa & Donnelly, 2019). Sahyoun and Magnan (2020) suggest that banks' audit committees increase voluntary disclosure whenever financial reporting quality is low.…”
Section: Methodsmentioning
confidence: 99%